Light spectra influence biomass and phenolics while sustaining high fucoxanthin in the tropical indigenous diatom Thalassiosira weissflogii - Tan, Hong Ning; Yeap, Swee Keong; Tan, Jian Ping; Fatimah, M. Yusoff; Malinna, Jusoh; Rahman, Norazira Abdu (PeerJ Inc., 2026)
Microalgae are promising sustainable sources of bioactive compounds for food and pharmaceutical applications. In this study, the tropical indigenous diatom Thalassiosira weissflogii TRG10-P105 (TW P105) was investigated under various light spectra to evaluate biomass and metabolite productivity for industrial cultivation. Cultures were grown under white, red, blue, combined red–blue, and white supplemented with UVA light, and assessed for growth, pigment composition, fucoxanthin (Fx), and total phenolic content (TPC). Broad-spectrum white light supported the highest growth (30.17 ± 2.06% d−1), biomass productivity, chlorophylls, carotenoids, and TPC (8.63 ± 0.07 mg GAE g−1 dw). Conversely, growth in the white-UV group was initially suppressed but resumed from day 5 onwards as UV-A was introduced, resulting in a specific growth rate (SGR) of 10.94 ± 3.96% d−1, biomass accumulation of 0.017 ± 0.00 g L−1, and productivity of 0.002 ± 0.000 g L−1 d−1. The reduced pigment content and TPC observed in the white–UV treatment suggest that the short UV-A exposure period (days 5–7) limited the induction of photoprotective and antioxidant responses. However, Fx levels remained consistently high across spectra (17.27–18.49 mg g−1 dw), indicating that TW P105 maintains near-maximal Fx accumulation even under low-light conditions or suppressive white-UV conditions (15.06 ± 0.69 mg g−1 dw). These values exceeded most previously reported values by 1.9–13.2 fold. Collectively, these findings show that spectral quality can be used to fine-tune phenolic and antioxidant production, while white light maximizes biomass, carotenoid, and TPC yields. This study provides a technical foundation for spectral control in large-scale algal production and supports the industrial potential of TW P105 as a scalable, cost-effective source of fucoxanthin-rich biomass for nutraceutical, functional food, and pharmaceutical applications.